Peran Mikrobiota dalam Kesehatan Manusia - fanani, silvi nuriyah (Maliki Interdisciplinary Journal, 2025)
The human microbiota is a community of microorganisms that live in the human body, especially in the digestive tract, and consists of various types of bacteria, viruses, fungi, and other microbes. Although these microorganisms are often associated with disease, recent scientific research has shown that microbiota play a vital role in maintaining a healthy body. Microbiota functions in digestion, vitamin production, protection against pathogens, and regulation of the immune system. In addition, microbiota also plays a role in maintaining mental balance through the gut-brain axis, a communication pathway between the central nervous system and microorganisms in the gut that influences psychological conditions such as depression and anxiety. Each individual has a unique microbiota composition, which is influenced by genetics, diet, lifestyle, age and environment. Imbalances in the microbiota, known as dysbiosis, can trigger a variety of health disorders, such as obesity, diabetes, autoimmune diseases, metabolic disorders and neurological disorders. The development of research on microbiota has opened up new opportunities in the field of disease treatment and prevention through a more personalized approach based on microbial balance. Therefore, a deeper understanding of the role of the microbiota is crucial in supporting the development of effective and sustainable health strategies.